Ten Indigenous Edible Plants: Contemporary Use in Eastern Crete, Greece - Psaroudaki, Antonia; Dimitropoulakis, Petros; Constantinidis, Theophanis; Katsiotis, Andreas; Skaracis, George N. (My University, 2012)
In the present study, ten species of indigenous edibleplants of Eastern Crete were collected, recorded, and botani-cally classiﬁed. Moreover, a survey study was conductedregarding the collection and use of edible wild greens intoday’s diet of the inhabitants of Eastern Crete. The resultsof the study showed that there is a positive correlationbetween the collection and consumption of edible wildplants and the age and profession of the collector. It wasalso clear that greens that are abundantly found and growin nearby areas are preferred. Older people identify andcollect a larger number of different species of plants com-pared with younger people. This fact demonstrates the riskof losing important nutritional information, although alarge percentage of the sample teaches others the art ofidentifying and collecting wild plants.
Keywords: Antioxidants; Edible wild plants; Mediterranean diet; Omega 3 fatty acids